Review on Profitability Difference among Large Commercial Banks: Evaluating Profitability Difference among Large Commercial Banks (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Banks and financial institutions are the backbone of the economy of the country everywhere in over the world. Profitability is one of the major criteria for evaluating the performance of a bank. Besides bank-specific factors, we include determinants of bank profitability and variable selection. The study final conclusion indicates that size effect exists, that small and medium sized banks exhibits higher overall performance compared to large banks.